Prevalence of Hypertension and Diabetes Mellitus in Political Cadres of Nepal - Paudel, Vijaya Prasad (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Hypertension and Diabetes Mellitus are both major modifiable risk factors leading to premature death due to cardiovascular and cerebrovascular diseases. Therefore, early diagnosis and treatment are must to reduce morbidity and mortality due to following diseases. Therefore authentic data on these issues are of great importance. The aim of this study was to address this gap and create awareness regarding essence of control of Diabetes and Hypertension among political cadres of Nepal as they play major role in policy making. Materials & Methods: A descriptive cross-sectional study in the political cadres of Nepal was conducted at Pragya Bhawan, Kathmandu on 4th March, 2012 where delegates attended their 3rd National assembly. Standard criteria were used to describe both Hypertension and Diabetes and their respective goals. Awareness and treatment were based on self-report. Results: A total of 291 subjects were included in the study. The prevalence of hypertension was 44.32% while that of Diabetes was 18.56%. The current blood pressure of the study population was 50% within normal range and 50% of them was above normal range, body mass index of 35% was normal and rest was above normal range. 15% of the study population was known diabetic while 33% was known hypertensive. More than 50% of known diabetics had poor control over blood sugar and 72% of the known hypertensive had poor blood pressure control. Conclusion: The scenario of hypertension and diabetes control among the political cadres is not up to the mark. Most of those already having the disease have poor control of blood pressure and blood sugar level. From this, the situation obviously seems more warning in general population and needs well-designed assessment.